Why People Believe in Their Leaders - Or Not - Chng, Daniel; Kim, Tae-Yeol; Gilbreath, Brad; Andersson, Lynne (MIT Sloan Management Review, 2018)
Organizations need to focus on how blockchain can be used to support their unique strategies. Without this focus, they risk investing in initiatives that don't provide meaningful value.